Bridging Technostress and AI Adoption in HR: A Moderated Mediation Study of Behavioural Intention and Support - Seshasai, Saladi Jaswanth; K.D, Balaji (Asian Journal of Interdisciplinary Research, 2026)
The paper delves into the implications of various forms of technostress, i.e. complexity, insecurity, uncertainty, and overload, on the usage of AI-based recruitment systems in information technology firms. It also examines the mediating and moderating factors behind the relationship (behavioral intention and organizational support respectively). The information was gathered through snowball sampling technique and 273 useful answers were obtained. The required sample size was determined using a standard sample size determination formula. SPSS and the PROCESS macro were used to conduct the analysis, and the tests involved reliability, Exploratory Factor Analysis (EFA), descriptive statistics, mediation, and moderation analysis. The findings revealed that all the variables were reliable and were merged into seven valid factors. The results of mediation affirmed that behavioral intention is a significant predictor of the relationship between technostress and actual usage of AI systems. The moderation outcomes indicated that organizational support mitigates the adverse influence of technostress on actual usage. The study is of value to HR professionals and decision-makers. Better acceptance and utilization of AI tools can be observed in organizations where the support of the organization is enhanced and the stress of the employees related to the technology is minimized. Consequently, this may contribute to the ease of digitalization, enhanced hiring rates, and employee trust in AI-based procedures.